Layered Sodium Titanate Nanostructures as a New Electrode for High Energy Density Supercapacitors - M. M., Yusoff; Rajan, Jose; K. F., Chong; Radhiyah, Abd Aziz; Izan Izwan, Misnon (Elsevier, 2013)
A flower-shaped hydrated layered sodium titanate material, Na2Ti2O4(OH)2, have been synthesized through a facile hydrothermal method and subsequently converted into sodium free titania (anatase). Potential application of the Na2Ti2O4(OH)2 as an electrode for supercapacitors under pseudo-capacitance storage mode is evaluated. The Na2Ti2O4(OH)2 showed sixfold higher specific capacitance (CS ∼ 300 F g−1) in an aqueous electrolyte than the anatase and demonstrated stable electrochemical cycling. This high CS is originated from a combination of electrochemical double layer and pseudo-capacitance storage mechanisms. The presence of hydrated layered within some loose interlayer plays an important role in assisting the diffusion process of ions as confirmed in electrical impedance spectroscopy analysis.